Uma "praia" nas Alterosas, uma "antena parabólica" ativista: configurações contemporâneas da contestação social de jovens em Belo Horizonte - Igor Thiago Moreira Oliveira (2012)
The contemporary world has seen the emergence of various social movements headed by young people. Since at least the late twentieth century to the first decade of the 2000s with the so-called anti-globalization movements have emerged around the globe multiple forms of agency youth protesters of the social order. In this context the object of this paper is to analyze a social movement that emerged starring young people in the city of Belo Horizonte in January 2010, the Praia da Estação. We believe that the Praia da Estação was a drive directly connected to the global context of contemporary social movements headed by young people on the one hand, and on the other, directly connected to the local context, where the city of Belo Horizonte on urban issues and questions of municipal Power. Our analysis then sought to give emphasis to the constitutive processes and characteristics of that movement in order to realize what it has to say about the social movement headed by young people nowadays and you have to say about the urban transformations in the city of Belo Horizonte. Developed and coordinated with the new technologies of communication and information, the Beach Station revealed to us an object of study of complex and difficult concept. We tried to analyze the participants' own definitions of the Beach Station on the move - protest, party, urban intervention, movement, civil disobedience, occupation of public space - from concepts originated from the literature on social movements and youth participation - new social movements movements, social networking, cyber-activism and youth autonomist. The survey was conducted from participant observation, interviews and netnography - ethnography of virtual spaces in which the Beach Station was set up specifically in the list and blog BH Square Free. We noticed that the Praia da Estação possesses characteristics common to many contemporary youth movements - horizontal, carnivalization protest, internet connection, network organization - and that brought up as one of its central concerns the problem of urban and municipal authorities.